Evaluation of heavy metal contamination of soil and the health risks in four potato-producing areas - Zhang, Jie; Liu, Ke; He, Xue; Li, Wei; Zhang, Meng; Cai, Quan (Frontiers in Environmental Science, 2023)
Areas polluted by heavy metals in soil may pose a major risk to human health and ecological environment safety. In this study, 89 soil samples were collected from four potato producing areas (Libo, Chishui, Panxian and Weining) in Guizhou Province, China, and the concentrations of 9 soil heavy metals were analyzed and measured. The aims of this study was to evaluate the human health risk and pollution index of heavy metals in the soil of some potato-producing areas in Guizhou Province by using the geoaccumulation index method, pollution load index method and health risk assessment method. The results revealed that Igeo<0 in Libo and Chishui, Igeo>0 in Panxian except Pb, The Igeo of As and Sb were less than 0 in Weining, and other elements were polluted to varying degrees. The pollution load index is Panxian (1.47) > Weining (1.39) > Libo (0.67), Chishui (0.67), Libo and Chishui were generally no polluted, soils in Panxian and Weining were polluted. The health risks of potatoes through food ingestion are less than 1. In terms of carcinogenesis, the risk of human in each study area through the ingestion was Cr > As > Cd. Cr and As would be produced certain carcinogenic risk to human through the dermal contact. Cr had a strong carcinogenic risk to adults through the inhalation. In terms of non-carcinogenesis, children in each study area had a strong risk under the each pathways. The risk of carcinogenesis in adults through inhalation pathway is greater than that in children, and the risk of carcinogenesis and non-carcinogenesis in children through Ingestion and dermal contact pathway is greater than adults. The results of this study suggest that attention should be paid to the remediation of heavy metals in contaminated soil to protect human health.